Ordered porous passivation layer and preparation method and application thereof
By adopting the preparation method of an ordered porous passivation layer in perovskite solar cells, the problems of passivation layer thickness control and porosity regulation are solved, and the expansion of charge transport channels and the improvement of battery performance are achieved.
Patent Information
- Application Number
- CN202411843782.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-14
- Publication Date
- 2025-03-25
AI Technical Summary
The passivation layer of the existing perovskite solar cells has problems such as thickness control, performance degradation under high temperature or long-term lighting conditions, and difficulty in controlling porosity.
Using the preparation method of an ordered porous passivation layer, a porous passivation layer with a highly ordered and controllable pore structure is constructed by combining the NiOx hole transport layer, a polystyrene nanosphere template layer and the Al2O3 passivation layer, and atomic layer deposition technology and spin coating technology.
The provision of additional charge transmission channels is achieved, breaking through the thickness limit of passivation layer, adjustable control of porosity is achieved, and the photoelectric conversion efficiency, stability and durability of perovskite solar cells is improved.
Smart Images

Figure CN119698203A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of perovskite solar cells, and in particular relates to an ordered porous passivation layer and a preparation method and application thereof. Background Art
[0002] Perovskite solar cells have attracted widespread attention in the photovoltaic field due to their excellent photoelectric conversion efficiency and low preparation cost. Perovskite solar cells have the characteristics of high extinction coefficient and high carrier mobility, which makes them have great potential in the field of photoelectric conversion. However, perovskite solar cells still face many challenges in the process of commercialization, among which defect passivation is one of the important means to improve their performance. By passivating the defects on the surface of perovskite films, non-radiative recombination can be reduced and the photoluminescence yield can be increased, thereby significantly improving the photoelectric conversion efficiency and stability of solar cells.
[0003] At present, the research on defect passivation of perovskite solar cells is mainly focused on the development and application of interface passivation layers. Traditional passivation layers usually adopt a planar structure and are deposited on the surface of perovskite films through solution treatment to form a thin molecular layer. These passivation materials include ammonium ligand salts with alkylammonium chains, cyclic or aromatic ammonium cations, and typical halide anions. These materials can bind to the perovskite surface through A-site vacancies or hydrogen bonds, effectively passivate surface defects, and improve the performance of solar cells. In addition, the two-dimensional perovskite passivation layer also shows great potential in inhibiting surface ion migration and improving device stability due to its unique structure and properties.
[0004] Although the traditional planar structure passivation layer has achieved certain results in improving the performance of perovskite solar cells, it still has some significant problems. First, the conductivity of the passivation material itself will have an adverse effect on charge transfer, so the thickness of the passivation layer needs to be strictly controlled. This strict requirement on thickness limits the scalability of the manufacturing process, making it challenging to produce perovskite solar cells on a large scale. Secondly, the traditional passivation layer is prone to performance degradation under high temperature or long-term light conditions, affecting the long-term stability of the device. In addition, although the two-dimensional perovskite passivation layer has excellent performance, its formation conditions are relatively harsh, and there are stability problems caused by cation migration, which requires further research and optimization. Summary of the invention
[0005] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide an ordered porous passivation layer and a preparation method and application thereof, so as to solve the technical problem of how to design an ordered porous passivation layer to provide additional charge transfer channels to break through the thickness limitation of the passivation layer and realize adjustable control of the porosity, thereby effectively improving the defect passivation of perovskite solar cells.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions: The invention discloses a method for preparing an ordered porous passivation layer, comprising the following steps: 1) NiO x The solution was spin-coated on the pretreated substrate and dried to obtain NiO x hole transport layer; 2) The polystyrene nanosphere suspension is evenly coated on the NiO x On the hole transport layer, after drying, an ordered template layer is formed; 3) An Al2O3 passivation layer is grown on the ordered template layer using an atomic layer deposition method; an ordered porous passivation layer is formed after heating.
[0007] Preferably, in step 1), NiO x The concentration of the solution is 3~15 mg / ml; the spin coating rate is 3000~5000 rpm; the spin coating time is 15~30 s; the drying temperature is 80~150°C, and the drying time is 5~30 min.
[0008] Preferably, in step 2), the method for preparing the polystyrene nanosphere suspension comprises: dispersing the polystyrene nanospheres in ultrapure water; the concentration of the polystyrene nanosphere suspension is 0.01-1 mg / ml.
[0009] Further preferably, in step 2), the particle size of the polystyrene nanospheres is 20-500 nm.
[0010] Preferably, in step 2), the coating conditions include: a spin coating rate of 3000-5000 rpm; a spin coating time of 15-30 s; The drying temperature is 80~100℃ and the drying time is 5~30min.
[0011] Preferably, in step 3), the thickness of the Al2O3 passivation layer is 2-300 nm.
[0012] Preferably, in step 3), the temperature of the heating treatment is 250-350° C. and the time of the heating treatment is 20-40 min.
[0013] The invention also discloses an ordered porous passivation layer, which is prepared by adopting the method for preparing the ordered porous passivation layer.
[0014] The present invention also discloses a perovskite solar cell, comprising: a substrate, a NiO x hole transport layer, ordered porous passivation layer, perovskite layer, electron transport layer and electrode layer; The ordered porous passivation layer is prepared by adopting the above-mentioned method for preparing the ordered porous passivation layer.
[0015] Preferably, the method for preparing the perovskite layer comprises: 0.25 FA 0.75 Pb(I 0.85 Br 0.15 )3, weighing FAI, CsI, PbBr2 and PbI2, and dissolving them in a mixed solution of DMF and DMSO to obtain a perovskite precursor solution, coating the perovskite precursor solution on the surface of the ordered porous passivation layer, and annealing to obtain a perovskite layer; In the mixed solution of DMF and DMSO, the volume ratio of DMF to DMSO is 4:(0-1); the annealing condition is annealing at 100-150 °C for 20-40 min; The preparation method of the electron transport layer includes: evaporating C60 on the perovskite layer to obtain electron transport; the thickness of C60 is 20~50nm, and the evaporation rate is 0.1~0.5 Å s -1 ; The preparation method of the electrode layer includes: evaporating a gold electrode on the electron transport layer to obtain the electrode layer; the thickness of the gold electrode is 60-120 nm, and the evaporation rate is 1-5 Å s -1 .
[0016] Compared with the prior art, the present invention has the following beneficial effects: The invention discloses a method for preparing an ordered porous passivation layer, NiO x As a hole transport layer material, its high carrier mobility and good chemical stability are the key to improving battery performance. The spin coating process can ensure that NiO x The solution evenly covers the substrate to form a continuous and dense film. During the drying process, the solvent evaporates and the NiO x The particles are closely arranged to form an efficient hole transport channel. This step provides a stable substrate for the subsequent template layer deposition and passivation layer growth, while ensuring the effective transmission of holes from the perovskite layer to the electrode, reducing the interface resistance and improving the photocurrent and open circuit voltage of the battery. The particle size and arrangement of polystyrene nanospheres as sacrificial templates directly determine the porosity and pore size distribution of the porous passivation layer. By precisely controlling the coating conditions and the concentration of nanospheres, the nanospheres can be deposited on the NiO xThe ordered template layer provides a precise mold for the subsequent growth of the Al2O3 passivation layer, so that the passivation layer can replicate the structure of the template layer to form an ordered porous passivation layer with highly ordered pores. The ordered porous passivation layer not only increases the path and surface area for charge transfer, but also helps to reduce the charge accumulation at the interface, thereby improving the filling factor and efficiency of the battery. The atomic layer deposition (ALD) technology, with its high precision and controllability, realizes the layer-by-layer growth of the Al2O3 passivation layer at the nanoscale. This layer-by-layer growth method ensures the uniformity and density of the passivation layer, avoiding the holes and defects that may occur in traditional deposition methods. As a passivation layer material, Al2O3 can effectively isolate electrons and holes with its high insulation and chemical stability, reducing charge recombination at the interface. At the same time, the ALD technology also allows the thickness of the passivation layer to be precisely controlled by adjusting the number of deposition cycles, further optimizing the performance of the battery. Heating treatment is a key step in removing the polystyrene template layer and forming an ordered porous passivation layer. At the appropriate temperature, the polystyrene balls will melt and volatilize, leaving pores opposite to the template layer structure. This porous structure not only increases the surface area and charge transfer path of the passivation layer, but also optimizes the charge transfer characteristics in the passivation layer through flexible regulation of the porosity. In addition, the porous structure is also beneficial to reduce stress concentration and crack generation at the interface, and improve the mechanical stability and durability of the battery. The present invention achieves precise regulation of the porosity, pore size and passivation layer thickness of the porous structure by precisely controlling the process parameters and material selection of each step. This porous passivation layer not only optimizes the charge transfer characteristics in the passivation layer, but also improves the photoelectric conversion efficiency, stability and durability of the battery, providing new ideas and technical approaches for improving the performance of perovskite solar cells.
[0017] The present invention also discloses an ordered porous passivation layer obtained by the above-mentioned preparation method. The ordered porous passivation layer is precisely constructed by a sacrificial template method and has a high degree of orderliness and a controllable pore structure. This structure not only provides more transmission channels for charges, but also optimizes the transmission path of the charges through precise regulation of the pores, reducing energy loss during the transmission process. The porous structure increases the surface area of the passivation layer, which is conducive to forming a closer contact with the perovskite layer, thereby reducing the charge recombination at the interface and improving the photoelectric conversion efficiency of the battery. The presence of pores also helps to relieve the stress generated by the battery during operation and improve the mechanical stability and durability of the battery. By adjusting the particle size, center spacing and thickness of the passivation layer of the polystyrene balls, the porosity and pore size of the porous structure can be flexibly regulated, providing more possibilities for optimizing battery performance.
[0018] The present invention also discloses a perovskite solar cell. When the ordered porous passivation layer prepared by the above preparation method is used in the preparation of the perovskite solar cell, the ordered porous passivation layer is an important component of the battery, and its unique pore structure optimizes the transmission characteristics of the charge, reduces the loss of the charge during the transmission process, thereby improving the photoelectric conversion efficiency of the battery. The existence of the passivation layer also effectively isolates electrons and holes, reduces the charge recombination at the interface, and further improves the performance of the battery. The porous structure helps to alleviate the thermal stress and mechanical stress of the battery during operation, reduces the cracks and failures of the battery caused by stress concentration, and improves the long-term stability of the battery. The passivation layer, as a protective layer, prevents the external environment from corroding the perovskite layer and prolongs the service life of the battery. By accurately controlling the porosity and pore size of the porous structure, the photoelectric performance of the battery, such as open circuit voltage, short circuit current and filling factor, can be optimized, so that the battery can maintain an efficient and stable working state under a wider range of lighting conditions and temperature. The ordered porous passivation layer also helps to improve the weather resistance and anti-aging performance of the battery, so that the battery can still maintain good performance in harsh environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 Schematic diagram of the ordered porous passivation layer disclosed in Example 1 of the present invention; wherein (a) is a front view; and (b) is a top view. DETAILED DESCRIPTION
[0020] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0021] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.
[0022] The present invention is further described in detail below in conjunction with the accompanying drawings: The invention proposes a method for preparing an ordered porous passivation layer, which accurately constructs a porous inorganic passivation layer through a sacrificial template method, aiming to optimize the charge transfer characteristics of perovskite solar cells and realize flexible regulation of porosity.
[0023] The present invention discloses a method for preparing an ordered porous passivation layer, which specifically comprises the following steps: 1) Preparation of NiO x Hole transport layer Select high quality NiO x Nanoparticles as raw materials.
[0024] NiO x The nanoparticles were evenly dispersed in deionized water and stirred thoroughly using a magnetic stirrer to ensure that the particles were evenly dispersed to form a stable aqueous solution of 3-15 mg / ml.
[0025] Use a spin coater and set the speed to 3000~5000rpm to coat the prepared NiO x The solution was spin-coated on the pretreated substrate FTO conductive glass, and the spin-coating time was 15~30s.
[0026] The spin-coated sample was placed in an oven and dried at 80-150°C for 5-30 min to remove the residual moisture and form a dense NiO x Hole transport layer.
[0027] 2) Preparation of template layer Polystyrene (PS) nanospheres were selected as sacrificial templates, and their particle size range was controlled between 20 and 500 nm to meet the requirements of different porosities.
[0028] The PS nanospheres were evenly dispersed in ultrapure water and the concentration was adjusted to 0.01~1 mg / ml to ensure the uniformity of the template layer.
[0029] The PS nanosphere suspension is evenly coated on the NiO x After drying, an ordered template layer is formed on the hole transport layer. The spin coating speed is set to 3000~5000rpm, the spin coating time is 15~30s; the drying temperature is 80~100℃, and the drying time is 5~30min.
[0030] 3) Preparation of passivation layer Atomic layer deposition of Al2O3 was used as the passivation layer, and the polystyrene template was removed by heating to 250-350℃ in toluene solution or air for 20-40min. Al2O3 was selected as the passivation layer material because of its good insulation and chemical stability.
[0031] Using atomic layer deposition (ALD) technology, the growth of Al2O3 is precisely controlled on the ordered template layer, and the thickness is controlled between 2 and 300nm. ALD technology can ensure the uniformity and thickness accuracy of the passivation layer.
[0032] The sample deposited with Al2O3 is placed in a toluene solution or air, heated to 250~350℃ and kept warm for 20~40min. The high temperature is used to decompose and volatilize the PS nanospheres, leaving an ordered porous structure to obtain an ordered porous passivation layer.
[0033] The present invention also discloses an ordered porous passivation layer, which is precisely constructed by a sacrificial template method and has a high degree of orderliness and controllable pore structure. By adjusting the particle size, center spacing and thickness of the polystyrene spheres, the porosity and pore size of the porous structure can be flexibly controlled, providing more possibilities for optimizing battery performance.
[0034] The present invention discloses a perovskite solar cell, comprising: a substrate, a NiO x Hole transport layer, ordered porous passivation layer, perovskite layer, electron transport layer and electrode layer.
[0035] NiO x The hole transport layer and the ordered porous passivation layer are prepared by the above preparation method.
[0036] The preparation method of the perovskite layer comprises: according to the stoichiometric ratio, FAI, CsI, PbBr2 and PbI2 are mixed in a stoichiometric ratio (Cs 0.25 FA 0.75 Pb(I 0.85 Br 0.15 )3) Weigh and dissolve in a mixed solvent of DMF and DMSO (the volume ratio of DMF and DMSO is 4: (0~1)) to form a 1.4M perovskite precursor solution. Use spin coating or scraping to evenly coat the perovskite precursor solution on the ordered porous passivation layer, and then anneal it at 100~150 ℃ for 20~40min; the precursor solution is crystallized to form a perovskite layer (Cs) with a band gap of 1.65eV. 0.25 FA 0.75 Pb(I 0.85 Br 0.15 )3), promoting the formation and crystallization of perovskite crystals.
[0037] The preparation method of the electron transport layer includes: evaporating C60 on the perovskite layer to obtain electron transport; the thickness of C60 is 20~50nm, and the evaporation rate is 0.1~0.5 Å s -1 , ensuring the efficient transmission of electrons in the battery.
[0038] The preparation method of the electrode layer includes: evaporating a gold electrode on the electron transport layer to obtain the electrode layer; the thickness of the gold electrode is 60-120 nm, and the evaporation rate is 1-5 Å s -1 , to form good electrical contact and current collection.
[0039] The invention proposes a method for preparing an ordered porous passivation layer, the key technical points of which are: 1. The porous structure provides additional charge transfer channels, breaking through the thickness limit of the passivation layer; 2. The porosity of the passivation structure can be adjusted by the particle size, center spacing and thickness of the passivation layer of the polystyrene spheres.
[0040] Example 1 A method for preparing an ordered porous passivation layer comprises the following steps: 1) Preparation of NiO x Hole transport layer Select high quality NiO x Nanoparticles are used as raw materials; NiO x The nanoparticles were evenly dispersed in deionized water and stirred thoroughly with a magnetic stirrer to ensure that the particles were evenly dispersed to form a 5 mg / ml stable aqueous solution. A spin coater was used with a speed of 4000 rpm to coat the prepared NiO x The solution was spin-coated on the pre-treated substrate FTO conductive glass for 20 seconds. The spin-coated sample was placed in an oven and dried at 120°C for 10 minutes to remove residual moisture and form a dense NiO x Hole transport layer.
[0041] 2) Preparation of template layer PS nanospheres were selected as sacrificial templates with a particle size range of 200 nm. The PS nanospheres were evenly dispersed in ultrapure water to obtain a PS nanosphere suspension with a concentration of 0.03 mg / ml to ensure the uniformity of the template layer. The spin coating method was used, with the spin coating speed set to 4000 rpm and the spin coating time set to 20 s. The PS nanosphere suspension was evenly coated on the NiO x On the hole transport layer, an ordered template layer was formed after drying at 90°C for 10 min.
[0042] 3) Preparation of passivation layer Atomic layer deposition of Al2O3 was used as the passivation layer, and then heated to 300℃ in air for 30 minutes to remove the polystyrene template. ALD technology was used to precisely control the growth of Al2O3 on the ordered template layer, with a thickness of 30nm. The PS nanospheres were decomposed and volatilized at high temperature, leaving an ordered porous structure, and an ordered porous passivation layer was obtained.
[0043] A method for preparing a perovskite solar cell, comprising: Step 1) to step 3) are the same as the above-mentioned method for preparing the perovskite battery transport layer.
[0044] 4) Preparation of perovskite layer According to the stoichiometric ratio, FAI, CsI, PbBr2 and PbI2 were mixed in a stoichiometric ratio (Cs 0.25 FA 0.75 Pb(I 0.85 Br 0.15 )3) Weigh and dissolve in a mixed solvent of DMF and DMSO (the volume ratio of DMF and DMSO is 4:1) to form a 1.4M perovskite precursor solution. Spin coating is used to evenly coat the perovskite precursor solution on the ordered porous passivation layer, followed by annealing at 100°C for 30 min; the precursor solution is crystallized to form a band gap of 1.65eV (Cs 0.25 FA 0.75 Pb(I 0.85 Br 0.15 )3) Perovskite layer.
[0045] 5) Preparation of electron transport layer Evaporation of C60 on the perovskite layer to obtain electron transport; the thickness of C60 is 30 nm and the evaporation rate is 0.3 Å s -1 , ensuring the efficient transmission of electrons in the battery.
[0046] 6) Preparation of electrode layer A gold electrode was evaporated on the electron transport layer to obtain an electrode layer; the thickness of the gold electrode was 100 nm and the evaporation rate was 2 Ås -1 , to form good electrical contact and current collection.
[0047] See also Figure 1 Schematic diagram of the ordered porous passivation layer disclosed in Example 1 of the present invention; wherein (a) is a front view; (b) is a top view; it can be seen from the figure that the porosity of the passivation structure is related to the particle size, center spacing and thickness of the passivation layer of the polystyrene spheres. The porosity of the porous structure can be precisely controlled by adjusting the particle size, center spacing and thickness of the Al2O3 passivation layer of the PS nanospheres. By changing these parameters, the porosity can be flexibly regulated in a wide range, thereby optimizing the charge transfer performance and battery performance.
[0048] Porosity = Sshadow / Sunit = =
[0049] Among them, S shadow is the pore area, S unit is the unit area, R is the distance between adjacent microspheres; r1 is the radius of the cross section between the microsphere and the upper surface of the passivation layer; r2 is the particle size of the microsphere; and h is the thickness of the passivation layer.
[0050] For example: when the particle size is 100nm, the center spacing is 300nm, and the thickness is 50nm, the porosity is about 10.07%; when the particle size is 100nm, the center spacing is 200nm, and the thickness is 50nm, the porosity is about 22.67%; when the particle size is 200nm, the center spacing is 400nm, and the thickness is 200nm, the porosity is about 90.69%.
[0051] Example 2 A method for preparing an ordered porous passivation layer comprises the following steps: 1) Preparation of NiO x Hole transport layer Select high quality NiO x Nanoparticles are used as raw materials; NiO x The nanoparticles were evenly dispersed in deionized water and stirred thoroughly with a magnetic stirrer to ensure that the particles were evenly dispersed to form a 3 mg / ml stable aqueous solution. A spin coater was used with a speed of 3000 rpm to coat the prepared NiO x The solution was spin-coated on the pre-treated substrate FTO conductive glass for 15 seconds. The spin-coated sample was placed in an oven and dried at 80°C for 5 minutes to remove residual moisture and form a dense NiO x Hole transport layer.
[0052] 2) Preparation of template layer PS nanospheres were selected as sacrificial templates with a particle size range of 20 nm. The PS nanospheres were evenly dispersed in ultrapure water to obtain a PS nanosphere suspension with a concentration of 0.01 mg / ml to ensure the uniformity of the template layer. The spin coating method was used, with the spin coating speed set to 3000 rpm and the spin coating time set to 15 s. The PS nanosphere suspension was evenly coated on the NiO x On the hole transport layer, an ordered template layer was formed after drying at 80°C for 5 min.
[0053] 3) Preparation of passivation layer Atomic layer deposition of Al2O3 was used as the passivation layer, and the solution was heated to 250℃ in a toluene solution for 20 minutes to remove the polystyrene template. The ALD technology was used to precisely control the growth of Al2O3 on the ordered template layer, with a thickness of 2nm. The PS nanospheres were decomposed and volatilized at high temperature, leaving an ordered porous structure, and an ordered porous passivation layer was obtained.
[0054] A method for preparing a perovskite solar cell, comprising: Step 1) to step 3) are the same as the above-mentioned method for preparing the perovskite battery transport layer.
[0055] 4) Preparation of perovskite layer According to the stoichiometric ratio, FAI, CsI, PbBr2 and PbI2 were mixed in a stoichiometric ratio (Cs 0.25 FA 0.75 Pb(I 0.85 Br 0.15 )3) Weigh and dissolve in DMF solvent to form a 1.4M perovskite precursor solution. Use a doctor blade coating method to evenly coat the perovskite precursor solution on the ordered porous passivation layer, and then anneal at 120 °C for 20 minutes; the precursor solution is crystallized to form a band gap of 1.65eV (Cs 0.25 FA 0.75 Pb(I 0.85 Br 0.15 )3) Perovskite layer.
[0056] 5) Preparation of electron transport layer Evaporation of C60 on the perovskite layer to obtain electron transport; the thickness of C60 is 20 nm and the evaporation rate is 0.1 Å s -1 , ensuring the efficient transmission of electrons in the battery.
[0057] 6) Preparation of electrode layer A gold electrode was evaporated on the electron transport layer to obtain an electrode layer; the thickness of the gold electrode was 60 nm and the evaporation rate was 1 Å s -1 , to form good electrical contact and current collection.
[0058] Example 3 A method for preparing an ordered porous passivation layer comprises the following steps: 1) Preparation of NiO x Hole transport layer Select high quality NiO x Nanoparticles are used as raw materials; NiO x The nanoparticles were evenly dispersed in deionized water and stirred thoroughly with a magnetic stirrer to ensure that the particles were evenly dispersed to form a 10 mg / ml stable aqueous solution. A spin coater was used with a speed of 3500 rpm to coat the prepared NiO xThe solution was spin-coated on the pre-treated substrate FTO conductive glass for 25 seconds. The spin-coated sample was placed in an oven and dried at 100°C for 20 minutes to remove residual moisture and form a dense NiO x Hole transport layer.
[0059] 2) Preparation of template layer PS nanospheres were selected as sacrificial templates with a particle size range of 100 nm. The PS nanospheres were evenly dispersed in ultrapure water to obtain a PS nanosphere suspension with a concentration of 0.5 mg / ml to ensure the uniformity of the template layer. The PS nanosphere suspension was evenly coated on the NiO x On the hole transport layer, an ordered template layer was formed after drying at 85 °C for 20 min.
[0060] 3) Preparation of passivation layer Atomic layer deposition of Al2O3 was used as the passivation layer, and the polystyrene template was removed by heating to 320℃ in air for 25 minutes. The growth of Al2O3 was precisely controlled on the ordered template layer using ALD technology, and the thickness was controlled to be 100nm. The PS nanospheres were decomposed and volatilized by high temperature, leaving an ordered porous structure, and an ordered porous passivation layer was obtained.
[0061] A method for preparing a perovskite solar cell, comprising: Step 1) to step 3) are the same as the above-mentioned method for preparing the perovskite battery transport layer.
[0062] 4) Preparation of perovskite layer According to the stoichiometric ratio, FAI, CsI, PbBr2 and PbI2 were mixed in a stoichiometric ratio (Cs 0.25 FA 0.75 Pb(I 0.85 Br 0.15 )3) Weigh and dissolve in a mixed solvent of DMF and DMSO (the volume ratio of DMF and DMSO is 4:1) to form a 1.4M perovskite precursor solution. Spin coating is used to evenly coat the perovskite precursor solution on the ordered porous passivation layer, followed by annealing at 130 °C for 25 min; the precursor solution is crystallized to form a band gap of 1.65 eV (Cs 0.25 FA 0.75 Pb(I 0.85 Br 0.15 )3) Perovskite layer.
[0063] 5) Preparation of electron transport layer Evaporation of C60 on the perovskite layer to obtain electron transport; the thickness of C60 is 40 nm and the evaporation rate is 0.2 Å s -1 , ensuring the efficient transmission of electrons in the battery.
[0064] 6) Preparation of electrode layer A gold electrode was evaporated on the electron transport layer to obtain an electrode layer; the thickness of the gold electrode was 80 nm and the evaporation rate was 3 Å s -1 , to form good electrical contact and current collection.
[0065] Example 4 A method for preparing an ordered porous passivation layer comprises the following steps: 1) Preparation of NiO x Hole transport layer Select high quality NiO x Nanoparticles are used as raw materials; NiO x The nanoparticles were evenly dispersed in deionized water and stirred thoroughly with a magnetic stirrer to ensure that the particles were evenly dispersed to form a 5 mg / ml stable aqueous solution. A spin coater was used with a speed of 5000 rpm to coat the prepared NiO x The solution was spin-coated on the pre-treated substrate FTO conductive glass for 30 seconds. The spin-coated sample was placed in an oven and dried at 150°C for 30 minutes to remove residual moisture and form a dense NiO x Hole transport layer.
[0066] 2) Preparation of template layer PS nanospheres were selected as sacrificial templates with a particle size range of 500 nm. The PS nanospheres were evenly dispersed in ultrapure water to obtain a PS nanosphere suspension with a concentration of 1 mg / ml to ensure the uniformity of the template layer. Spin coating was used with a spin coating speed of 5000 rpm and a spin coating time of 30 s. The PS nanosphere suspension was evenly coated on the NiO x On the hole transport layer, an ordered template layer was formed after drying at 100°C for 30 min.
[0067] 3) Preparation of passivation layer Atomic layer deposition of Al2O3 was used as the passivation layer, and the polystyrene template was removed by heating to 350℃ in air for 40 minutes. The growth of Al2O3 was precisely controlled on the ordered template layer using ALD technology, and the thickness was controlled at 300nm. The PS nanospheres were decomposed and volatilized by high temperature, leaving an ordered porous structure, and an ordered porous passivation layer was obtained.
[0068] A method for preparing a perovskite solar cell, comprising: Step 1) to step 3) are the same as the above-mentioned method for preparing the perovskite battery transport layer.
[0069] 4) Preparation of perovskite layer According to the stoichiometric ratio, FAI, CsI, PbBr2 and PbI2 were mixed in a stoichiometric ratio (Cs0.25 FA 0.75 Pb(I 0.85 Br 0.15 )3) Weigh and dissolve in a mixed solvent of DMF and DMSO (the volume ratio of DMF and DMSO is 4:1) to form a 1.4M perovskite precursor solution. Spin coating is used to evenly coat the perovskite precursor solution on the ordered porous passivation layer, followed by annealing at 150 °C for 40 min; the precursor solution is crystallized to form a band gap of 1.65 eV (Cs 0.25 FA 0.75 Pb(I 0.85 Br 0.15 )3) Perovskite layer.
[0070] 5) Preparation of electron transport layer Evaporation of C60 on the perovskite layer to obtain electron transport; the thickness of C60 is 50 nm and the evaporation rate is 0.5 Å s -1 , ensuring the efficient transmission of electrons in the battery.
[0071] 6) Preparation of electrode layer A gold electrode was evaporated on the electron transport layer to obtain an electrode layer; the thickness of the gold electrode was 120 nm and the evaporation rate was 5 Ås -1 , to form good electrical contact and current collection.
[0072] The invention proposes a method for preparing an ordered porous passivation layer, which adopts a sacrificial template method to prepare an ordered porous inorganic passivation layer. The porous structure provides a charge transfer channel, and the porosity is adjustable, which solves the thickness dependence of the passivation layer. The performance of perovskite solar cells is significantly improved. Due to the conductivity limitation of the material itself, the thickness of the traditional planar passivation layer often needs to be strictly controlled to avoid adverse effects on charge transfer. The ordered porous passivation layer proposed in the invention provides an additional transmission channel for the charge by introducing pores. These channels can bypass the passivation material itself, reduce the resistance of charge transfer, and thus improve the charge collection efficiency and the photoelectric conversion efficiency of the battery. Porosity is an important factor affecting the performance of porous structures. The invention realizes flexible regulation of porosity in a wide range by adjusting the particle size, center spacing and thickness of the passivation layer of the polystyrene spheres. This allows researchers to optimize the pore structure according to specific needs to achieve the best charge transfer effect and battery performance. Different perovskite solar cell application scenarios may have different requirements for porosity. The preparation method of the present invention can easily adjust the porosity, so that the technology has stronger adaptability and application range. Due to the thickness limitation of the traditional passivation layer, it is often difficult to maintain uniformity and stability in large-scale production. The ordered porous passivation layer of the present invention reduces the strict requirements on the thickness of the passivation layer by providing an additional charge transfer channel. This makes it easier to maintain the uniformity and stability of the passivation layer when producing perovskite solar cells on a large scale, and improves the scalability of the manufacturing process. The porous structure can more effectively passivate the defects on the surface of the perovskite film and reduce the occurrence of non-radiative recombination. This helps to reduce the dark current of the battery, increase the open circuit voltage and fill factor, and thus improve the overall performance of the battery. The porous structure may also help to improve the weather resistance of the battery. By optimizing the pore structure, the influence of the external environment (such as humidity, temperature, etc.) on the inside of the battery can be slowed down, and the service life of the battery can be extended. The preparation method of the present invention is relatively simple and easy to control. By adjusting several key parameters (such as the particle size of the polystyrene spheres, the center spacing and the thickness of the passivation layer), the construction of the porous structure and the regulation of the porosity can be achieved. This helps to simplify the preparation process, improve production efficiency and reduce production costs. The method for preparing the ordered porous passivation layer disclosed in the present invention provides additional charge transfer channels, realizes flexible regulation of porosity, breaks through the thickness limitation of the passivation layer, improves battery stability and simplifies the preparation process, thus providing new ideas and technical approaches for the performance optimization and commercial application of perovskite solar cells.
[0073] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A method for preparing an ordered porous passivation layer, characterized in that: The following steps are involved: 1) NiO x The solution was spin-coated on the pretreated substrate and dried to obtain NiO x hole transport layer; 2) The polystyrene nanosphere suspension is evenly coated on the NiO x On the hole transport layer, after drying, an ordered template layer is formed; 3) An Al2O3 passivation layer is grown on the ordered template layer using an atomic layer deposition method; an ordered porous passivation layer is formed after heating.
2. The method for preparing an ordered porous passivation layer according to claim 1, characterized in that: In step 1), the NiO x The concentration of the solution is 3-15 mg / ml; the spin coating speed is 3000-5000 rpm; the spin coating time is 15-30 s; the drying temperature is 80-150° C., and the drying time is 5-30 min.
3. The method for preparing an ordered porous passivation layer according to claim 1, characterized in that: In step 2), the preparation method of the polystyrene nanosphere suspension includes: dispersing polystyrene nanospheres in ultrapure water; the concentration of the polystyrene nanosphere suspension is 0.01-1 mg / ml.
4. The method for preparing an ordered porous passivation layer according to claim 3, characterized in that: In step 2), the particle size of the polystyrene nanospheres is 20-500 nm.
5. The method for preparing an ordered porous passivation layer according to claim 1, characterized in that: In step 2), the coating conditions include: a spin coating rate of 3000-5000 rpm; a spin coating time of 15-30 s; The drying temperature is 80-100° C., and the drying time is 5-30 minutes.
6. The method for preparing an ordered porous passivation layer according to claim 1, characterized in that: In step 3), the thickness of the Al2O3 passivation layer is 2-300 nm.
7. The method for preparing an ordered porous passivation layer according to claim 1, characterized in that: In step 3), the temperature of the heating treatment is 250-350° C. and the time of the heating treatment is 20-40 min.
8. An ordered porous passivation layer, characterized in that: The ordered porous passivation layer is prepared by the method for preparing the ordered porous passivation layer according to any one of claims 1 to 7.
9. A perovskite solar cell, characterized in that: include: A substrate, a NiO x hole transport layer, ordered porous passivation layer, perovskite layer, electron transport layer and electrode layer; The ordered porous passivation layer is prepared by the preparation method according to any one of claims 1 to 7.
10. The perovskite solar cell according to claim 9, characterized in that: The preparation method of the perovskite layer comprises: 0.25 FA 0.75 Pb(I 0.85 Br 0.15 )3, weighing FAI, CsI, PbBr2 and PbI2, and dissolving them in a mixed solution of DMF and DMSO to obtain a perovskite precursor solution, coating the perovskite precursor solution on the surface of the ordered porous passivation layer, and annealing to obtain a perovskite layer; In the mixed solution of DMF and DMSO, the volume ratio of DMF to DMSO is 4:(0-1); the annealing treatment condition is annealing at 100-150°C for 20-40 min; The preparation method of the electron transport layer comprises: evaporating C60 on the perovskite layer to obtain electron transport; the thickness of the C60 is 20-50 nm, and the evaporation rate is 0.1-0.5 Å s -1 ; The preparation method of the electrode layer comprises: evaporating a gold electrode on the electron transport layer to obtain the electrode layer; the thickness of the gold electrode is 60-120 nm, and the evaporation rate is 1-5 Å s -1 .